Physical therapists' evidence-based practice profile and perspectives of entry-level EBP education: a mixed methods study in the Philippines. (3rd October 2022) - Rotor, Esmerita R.; Palad, Yves Y.; Cayco, Christopher S.; Perez, Krysta; Tiu, Christl; Gorgon, Edward
ABSTRACT: Background and Purpose: Inclusion of evidence-based practice (EBP) in entry-level physical therapy (PT) curricula is meant to develop the necessary competencies for better EBP uptake in clinical practice. This study aimed to: 1) determine the practice, knowledge, and values for EBP of the graduates of an entry-level PT curriculum with EBP education; 2) compare graduates' EBP practice profile to their EBP knowledge and values; and 3) explore their views on their EBP education and how EBP education influenced their practice. Methods: A convergent parallel design was used to gather quantitative and qualitative data. The Evidence-based Practice Profile - 2 (EBP 2 ) questionnaire was used for quantitative data. Focus group discussions and open-ended questions in the EBP 2 were sources for qualitative data. Results: Seventy-seven completed the questionnaire and eight participated in focus group discussions. Participants scored highest for Relevance domain (standardized mean = 75.3) and lowest for Practice (standardized mean = 45.5). Three themes, 'Positive impact of EBP education, ' 'Realities of PT clinical practice, and 'Strategies to improve EBP education' were derived. Data integration confirmed findings that graduates have good knowledge, value for, and confidence in doing EBP Discussion and Conclusion: Findings suggest that early EBP education led to adequate knowledge, confidence, and positive attitudes, but practice barriers hinder EBP uptake. The medical model of service delivery was identified as a factor that influences EBP use. There is a need to revisit the EBP education program to complement real-world demands.